A training program based on modern strategies in developing Diwani calligraphy skills for female students (Journal of the College of Basic Education, 2023)
Research abstract The current research aims to identify (a training program based on modern strategies in developing Diwani calligraphy skills among female students of the Institute of Fine Arts). Where the problem of the research was determined by the weak skills of Diwani calligraphy among the female students, it included purely the third stage students / the Institute of Fine Arts. They were chosen in an intentional way and two tools of research were adopted (the cognitive test and the skill test tool) in its design and found for them honesty and stability, and then used the appropriate statistical means and concluded that there is a great impact of the training program based on modern strategies in developing Diwani calligraphy skills, and accordingly the researcher recommended its adoption. Death Keywords: training program, Diwani calligraphy skills, modern strategies.